Does Foodservice Employees’ Burnout Influence Their In-role and Extra-role Food Safety Behaviors? A Structural Modeling Approach - Choi, Jihee (Journal of food protection, 2024)
•Employees’ colleague-related burnout and work-related burnout were negatively related to their job commitment in the foodservice industry.•Employees’ job commitment was positively correlated with their in-role food safety behaviors, such as compliance with food safety-related standards within their formal job tasks.•Employees’ job commitment was positively correlated with their extra-role food safety behaviors, including voluntary participation in food safety-related error management. Over the past decade, a number of previous studies have found a gap between employees’ food safety knowledge and their food safety behavior. Thus, it is valuable to examine motivators (or demotivators) of employees’ food safety behavior from a psychological perspective. The objective of this study is to investigate the relationships among employees’ burnout, job commitment, and food safety behaviors (in-role and extra-role). A total of 267 nonmanagerial restaurant employees participated in this study. The data were analyzed using structural equation modeling (SEM). Findings reveal that colleague-related burnout and work-related burnout negatively affect employee job commitment. In addition, employee job commitment is a major predictor of in-role and extra-role food safety behaviors. The findings shed light on the effect of different types of burnout on food safety behaviors, which in turn have significant implications for managers in the foodservice industry.